2021
DOI: 10.48048/tis.2021.701
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, in silico Studies, and Anticonvulsant Activity of 1,3,4-Oxadiazole Derivatives

Abstract: The title compounds 1,3,4-oxadiazole derivatives (C1-5) were synthesized by the cyclization of 4-hydroxy benzhydrazide (1) with various substituted aromatic aldehydes (2) in the presence of ceric ammonium nitrate. The structures of the newly synthesized compounds were established based on FT-IR, 1H-NMR, and Mass spectral data. In silico analysis was carried out using the Schrodinger 2018-3 suite device Maestro and docked to the binding site of the Human GABAA receptor (PDB ID:4COF). The toxicity of the compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The oxadiazole moiety is considered to have varied medicinal actions like anti-alzheimer [30,32], anti-inflammatory [33], antimicrobial [34], antimalarial [35], antidepressant [36], analgesic [37], anticancer [38] and antiviral [39], etc. Also, the multifunctional nature of the 1,3,4-oxadiazole nucleus with different substitutions has been reported for significant anticholinesterase and antioxidant activities [32,40].…”
Section: Synthesis and Evaluation Of Aminothiazole Hybrids As Potenti...mentioning
confidence: 99%
“…The oxadiazole moiety is considered to have varied medicinal actions like anti-alzheimer [30,32], anti-inflammatory [33], antimicrobial [34], antimalarial [35], antidepressant [36], analgesic [37], anticancer [38] and antiviral [39], etc. Also, the multifunctional nature of the 1,3,4-oxadiazole nucleus with different substitutions has been reported for significant anticholinesterase and antioxidant activities [32,40].…”
Section: Synthesis and Evaluation Of Aminothiazole Hybrids As Potenti...mentioning
confidence: 99%
“…SAR study of these derivatives indicated that only those compounds with electron‐donating capacity showed moderate activity, while the electron‐withdrawing groups showed weak activity in the protein denaturation assay. [ 39 ]…”
Section: Overview Of the Diverse Derivatives And Their Activitiesmentioning
confidence: 99%
“…SAR study of these derivatives indicated that only those compounds with electron-donating capacity showed moderate activity, while the electron-withdrawing groups showed weak activity in the protein denaturation assay. [39] Basappa et al synthesized a number of substituted 3-(5-phenyl-1,3,4-oxadiazol-2-yl)−2H-chromene-2-ones using a grinding approach with substituted aldehydes and analogs of hydrazine hydrates in the presence of iodine, which facilitates the process of cyclization. The synthesized chemical structures were assessed using spectroscopic techniques such as IR, 1 H NMR, 13 C NMR, and LCMS.…”
mentioning
confidence: 99%